Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

High-entropy superparaelectrics enhanced capacitive energy storage - Huifen Yu; Yunxuan Ji; Xinyu Cui; He Qi; Di Zhou; Liang Chen; Jun Chen (Chemical Engineering Journal, 2026)

Valorization of microalgal lipids for the production of high-value bio-based epoxidized monomers - Jiarong Tian; Siyuan Zhang; Yue Liu; Wei Rao; Kuichuan Sheng; Jun Wang; Yu Tang; Shaoqing Cui (Biomass and Bioenergy, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Conversion of biomass ash into cementitious materials with dicalcium silicate for soil stabilization - Qiyong Zhang; Zefa Lu; Jun Bi; Xiaoniu Yu; Bingxiang Yuan; Linyong Cui (Chemical Engineering Journal, 2026)

4,4′-dimethoxychalcone induces thermosensitive impairment of SIRT3-associated mitochondrial signaling and apoptotic cell death with therapeutic potential in cancer - Yu Song; Qing-Li Zhao; Ryohei Ogawa; Tatsuji Mizukami; Yu-Mei Li; Song-Ji Zhao; Zheng-Guo Cui; Jun-Ichi Saitoh; Kyo Noguchi (Chemico-Biological Interactions, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Towards intensified oxidative coupling of methane in engineered non-uniform temperature fields - Xiaoyu Cui; Jincheng Huang; Yu Fu; Jun Zhang; Yuhan Sun (Chemical Engineering Journal, 2026)

Properties of calcareous sand treated by seawater-based biomineralization via bacterial-enzyme induced carbonate precipitation - Ming-Juan Cui; Jian-Bin Wu; Han-Jiang Lai; Jun-Jie Zheng; Zhen Wu; Ye-Wei Zheng; Yan Luo; Wen-Yu Yang (Transportation Geotechnics, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Investigation on the density homogenization and swelling pressure evolution of compacted bentonite with technological voids based on friction analysis - Jing Ma; Yong-gui Chen; Yu-jun Cui; Zhao Sun; Wei-min Ye; Qiong Wang (Bulletin of Engineering Geology and the Environment, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Cerrena unicolor laccases as sustainable biocatalysts for detoxifying hazardous long-chain phthalates and deconstructing plastic mulch films - Long-Bin Zhang; Jun Kang; Xiu-Gen Qiu; Zhou Cui; Yu-Tian Li; Yan Zheng; Yu Li; Yi Guan; Juan-Juan Yang; Chun Meng (Journal of Environmental Management, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

A new fatty acid derivative derived from the deep-sea fungus Aspergillus sp. SCSIO41324 - Yu-Shi Chen; Ying-Ying Song; Sheng-Yi Deng; Xin-Kai Xiao; Xiao-Yan Pang; Wei-Jia Zhang; Yong-Hong Liu; Hong-Hua Cui; Jun-Feng Wang (Natural Product Research, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

A full active pharmaceutical ingredients-based nanoplatform potentiates tumor immunotherapy via multidimensional cGAS-STING pathway activation - Jun Wang; Jun Yin; Tao Kuang; Zhi Zheng; Yin Liu; Xiaofei Liu; Sha Liu; Suisui He; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Impact of node restriction on Cd and Zn transportation in wheat plant treated with swine manure and its biochar: a field experiment - Zhonghua Cui; Yu Pan; Zhangtao Li; Jian Liu; Alexandru Ozunu; Jun Meng; Kiril Manevski; Shengdao Shan (Food Chemistry, 2026)

Modelling swelling pressure evolution of compacted bentonite considering wetting-induced collapse in a dual-porosity framework - Jing Ma; Yong-gui Chen; Yu-jun Cui; Wei-min Ye; Qiong Wang (Engineering Geology, 2026)

Scutellarin reduces apoptosis in R28 cells induced by continuous hydrostatic pressure combined with oxygen-glucose deprivation through the Keap1/Nrf2/NF-κB pathway - Hongda Cui; Yu Huang; Xin Xia; Jiangwei Li; Jun Peng; Yijing Yang; Qinghua Peng (Tissue and Cell, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The performance and mechanism of sodium carboxymethyl cellulose in promoting the anaerobic ammonium oxidation coupled with Fe (III) reduction - Hong-Yan Meng; Shen Cui; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Pan Liang; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Sulfide geochemistry and gold occurrence in the Yu'erya deposit, Eastern Hebei, China: Implications for mineralization and metallurgy - Liangjie Cui; Qihai Shu; Yue He; Di Zhao; Fan Yu; Litian Zhang; Qingfei Wang; Jun Deng (Journal of Geochemical Exploration, 2026)

Temporal dynamics of insecticide-resistance mutations in the diamondback moth Plutella xylostella (Linnaeus, 1758) within northern immigration regions - Ya-Jun Qu; Jin-Cui Chen; Hui-Juan Li; Shuai-Yu Wang; Xue-Yan Zhang; Ary A. Hoffmann; Sen-Shan Wang; Shu-Jun Wei (Journal of Asia-Pacific Entomology, 2026)

Single-nucleus RNA sequencing reveals the underlying roadmap of early gonadal differentiation in teleost - Jialin Wang; Yajuan Huang; Zhongkai Cui; Kaili Zhang; Na Wang; Jun Luo; Yu Song; Bowen Hu; Ming Li; Yadong Chen; Manfred Schartl; Songlin Chen (Science China Life Sciences, 2026)

Policy for strengthening marine strategic science and technology capabilities: framework, theory, and practice - Zi Jun Hu; Wang Lai Cui; Bo Jun Gu; Xiao Yu Cui (Frontiers in Marine Science, 2026)
Policy for strengthening marine strategic science and technology capabilities have emerged as a new approach to overcoming the ‘bottleneck’ technology challenges in the marine sector, which have been exacerbated by technological blockades imposed by developed countries. This paper provides a comprehensive analysis of such policies from multiple dimensions, including their conceptual connotations, key components, main characteristics, theoretical interpretations, and practical applications. The study identifies five major policy directions that have emerged globally: breakthroughs in ‘bottleneck’ technologies, enhancement of maritime military capabilities, deep-sea resource development, marine industry innovation, and the strengthening of maritime governance and capacity building. These practices also exhibit a clear pattern of “development-stage alignment,” whereby high-income countries or regions focus on “innovation upgrading + hegemony maintenance,” while middle- and low-income countries or regions prioritize “basic capacity building + security assurance.” The core contribution of this article lies in constructing a systematic analytical framework of “concept-elements-characteristics-theory-practice” for such policies, clarifying their theoretical underpinnings and practical logic, and providing latecomer countries with a directly applicable theoretical framework and practical pathways for formulating marine strategic science and technology policies that are suited to their specific development stages.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Effects of different iron compounds on the acclimation of Feammox sludge: Nitrogen-iron transformation, sludge physicochemical properties, and microbial communities - Pan Liang; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Hong-Yan Meng; Shen Cui; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Unlocking Kluyveromyces marxianus for efficient protein expression and single-cell protein production - Fengjie Cui; Yuzhou Cao; Xuan Lou; Jun Liu; Aiqun Yu; Ning Xu (Bioresource Technology, 2026)

Neolithic genomes reveal long distance interactions in agropastoral border zone of Yan Mountain Region - Daxuan Zhang; Bing Sun; Fajun Li; Xue Zhao; Zhanhu Zhao; Jun Li; Shizhu Gao; Yu Li; Qiankun Quan; Natalia Berdnikova; Ivan Berdnikov; Shan Chen; et al. (Science Bulletin, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

A nitric oxide-based Ca2+ nanomodulator induces sustained calcium overload via respiratory inhibition for enhanced cancer immunotherapy - Zongtao Zhou; Hui Hu; Yi Li; Lijiao Yang; Suisui He; Jun Wang; Jinjin Chen; Zhijun Zhang; Jie Li; Xinping Liu; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Full-enzymatic three-in-one cascade finishing for woolen textiles: anti-felting, low-temperature dyeing and antibacterial processing - Jiaqi Zhang; Leilei Wu; Jun Wang; Li Cui; Ying Liu; Yuanyuan Yu; Qiang Wang; Ping Wang (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Surface engineering of MOF-derived hierarchical porous carbons for ultrasensitive detection and discrimination of anticancer and antibacterial drugs - Junlin He; Jun Wang; Zhonghui Luo; Jiaheng Zhang; Yongrong Deng; Bo Liu; Hui Zhao; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

Pinocembrin Alleviates Postoperative Cognitive Dysfunction in Aged Mice by Modulating miR-384-5p/FZD1 Axis to Activate the Wnt/β-Catenin Pathway - Jie Li; Xue-li Peng; Xin-yu Cheng; Jun-jun Yang; Cui Cui; Jian-hui Liu (Molecular Neurobiology, 2025)

The prospect of applying electrodialysis coupled three-dimensional electrode system to the treatment of organic wastewater containing high chloride salts - Haomiao Yu; Jun Cui; Hailong Tian; Dayang Yu (Process Safety and Environmental Protection, 2025)

Secondary risks of polymeric products produced by persulfate-based oxidation technologies: Enhanced iodination kinetics and more toxic disinfection by-products - Zhi Gao; Lu Wang; Xian-Shi Wang; Xiao-Na Zhao; Chong-Wei Cui; Jun Ma; Qing-Liang Liu; Yu-Lei Liu (Journal of Water Process Engineering, 2025)

A hydraulic conductivity model for unsaturated bentonite-based materials incorporating surface enhanced vapour diffusion - Zhang Rong LIU; Yu Jun CUI; Wei Min YE; Yong Gui CHEN; Qiong WANG (Computers and Geotechnics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Production of docosahexaenoic acid from corncob residue wastes through integrated whole-cell lignocellulosic saccharification and lipid fermentation by Aurantiochytrium - Xiaojin Song; Weijian Wan; Yuedong Zhang; Guang Yu; Bin Li; Qiu Cui; Ya-Jun Liu; Yingang Feng (Bioresource Technology, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Optimal path planning and navigation platform development for unmanned surface vehicles in complex inland waterways using a potential ant-colony algorithm - Peiyin Yuan; Yuan Li; Jun Cui; Yufeng Li; Jun Zhang; Yu Zhao (Ocean Engineering, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

A machine learning-assisted electrochemical nanosensor based on bimetal-codoped MOF composites for simultaneous detection and removal of multiple fluoroquinolone antibiotics - Suisui He; Jiaheng Zhang; Junlin He; Zhonghui Luo; Wen Chen; Huimin Tang; Jiaqi Long; Jun Wang; Hua Wei; Cui-Yun Yu (Journal of Cleaner Production, 2025)

Enhancing Feammox efficiency through riboflavin and humic acid: Nitrogen and iron transformation, energy metabolism, and microbial response - Dun Guo; Lei Yang; Hao-Qi Lu; Yu-Chao Wang; Hong-Yan Meng; Pan Liang; Shen Cui; Zhang-Wei He; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Hydro-mechanical behavior of compacted GMZ bentonite blocks with a vertical technological void - Jing Ma; Yong-gui Chen; Yu-jun Cui; Wei-min Ye; Qiong Wang (Engineering Geology, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Effect of kaempferol from Acori Tatarinowii Rhizoma (ATR) on grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Jun Cui; Qin Fan; Ruoxiao Zhang; Zihao Zhao; Yibo Hu; Ziquan Yu; Ning Jiang (Marine Life Science & Technology, 2025)

Occurrence, source, and ecological impacts of dry depositing aerosol metal elements in the Bohai Bay - Liying Peng; Xudong Cui; Xueou Wang; Yu Guo; Xing Ma; Yujian Wen; Zhi Wang; Yiyan Guo; Jun Sun (Marine Environmental Research, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

The transferrin a signaling pathway mediates uranium-induced hematopoietic dysfunction - Jin Gao; Fajian Luo; Qiu Chen; Na Chen; Jun Wan; Liang Sun; Yiyao Cao; Hong Ren; Yu Tu; Haiwen Huang; Fengmei Cui (Environmental Pollution, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Monitoring the Effects of Alkalinity on the Self-sealing of the Opalinus Clay from the Lower Sandy Facies (LSF) of Mont Terri Site Through Hydraulic Conductivity Test and μ-CT Observation - Yara Barakat; Nadia Mokni; Yu Jun Cui; Baptiste Chabot; Frédéric Bernier (Rock Mechanics and Rock Engineering, 2025)

Amyotrophic Lateral Sclerosis and Parkinson's Disease: Brain Tissue Transcriptome Analysis Reveals Interactions - Zewei Fu; Baofeng Feng; Herman Yao Akogo; Jiajia Ma; Yukun Liu; Hezhi Quan; Xiaohan Zhang; Yu Hou; Xuecong Zhang; Jun Ma; Huixian Cui (Molecular Neurobiology, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Roles of iron (V) and iron (IV) species in ferrate-triggered oxidation of phenolic pollutants and their transformation induced by phenoxyl radical - Xiao-Na Zhao; Zhuang-Song Huang; Yu-Lei Liu; Hai-Teng Gu; Zhi Gao; Chongwei Cui; Jun Ma; Lu Wang (Water Research, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Treatment of landfill leachate by two-stage electrochemical combination technology - Cui Liu; Dong Li; Jiahui Li; Chengqian Zhao; Xiaojing Liu; Xiao Huang; Feng Yin; Wei Shi; Jianghua Yu; Jun Wu; Jian Lu (Journal of Environmental Chemical Engineering, 2025)

Elucidation of the stress mechanisms on activated sludge stability induced by yttrium oxide nanoparticles with cytotoxicity: Performance deterioration, biointerface variation and microbial response - Shen Cui; Lei Yang; Haoqi Lu; Linkai Guo; Yuchao Wang; Jun Lan; Yong-Xiang Ren; Yu-You Li (Bioresource Technology, 2025)

Latitudinal distribution and propagation of lightning-generated whistler: A statistical study by Van Allen Probes observation and ray-tracing simulation - Zhaoguo He; Jiang Yu; Xiangling Ding; Zuzheng Chen; Nigang Liu; Yuguang Ye; Jun Cui; Qiugang Zong (Science China Earth Sciences, 2025)

Compressive stress induced by desiccation shrinkage in clayey soils - Hao Zeng; Chao-Sheng Tang; Yu-Jun Cui; Abdallah Najdi (Applied Clay Science, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Experimental investigation on swelling and gas breakthrough properties of GMZ bentonite considering alkaline solution effects - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Bao Chen; Yu-Jun Cui (Engineering Geology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Raman spectral optimization for soot particles: A comparative analysis of fitting models and machine learning enhanced characterization in combustion systems - Longfei Chen; Yang Cao; Xuehuan Hu; Bin Zhang; Xiaoyang Chen; Boxuan Cui; Jun Xu; Tao Yu; Zheng Xu (Building and Environment, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Phenols coupled during oxidation upstream of water treatment would generate higher toxic coupling phenolic disinfection by-products during chlorination disinfection - Zhi Gao; Yu-Lei Liu; Xian-Shi Wang; Xiao-Na Zhao; Zhi-Yu Zhu; Cai-Ni Ma; Chong-Wei Cui; Jun Ma; Lu Wang (Journal of Hazardous Materials, 2025)

Dynamic evolution of volatile compounds during cold storage of sturgeon fillets analyzed by gas chromatography-ion mobility spectrometry and chemometric methods - Jia-hua Yang; Shan Cui; Mei-jun Sun; Kai Liu; Hao Tao; Dan Zhang; Zi-heng Yan; Chun-yu Kang; Chun-qing Zhao (Food Chemistry, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Correlation Between Effector Gene Expression Targeted by lncRNAs in the Oomycete Fish Pathogen, Saprolegnia parasitica - Lijuan Liao; Zihao Zhao; Ruoxiao Zhang; Chaoqun Luo; Yibo Hu; Ziquan Yu; Jun Cui (Marine Biotechnology, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Buckling Failure of Multi-layer Surrounding Rock: Insights from Flexural Test of Laminated Plates Under Multi-directional Constraints - Yang-Yang Cui; Yang-Yi Zhou; Xiao-Jun Yu; Jian-Po Liu (Rock Mechanics and Rock Engineering, 2025)

Elucidation of microscopic mechanisms of tweens on whipping capabilities of aerated emulsions: Fat crystal-membrane interaction perspective - Pengkai Xie; Limin Cui; Mingdi Yu; Yulong Shao; Abdelaziz Elbarbary; Qingzhe Jin; Xingguo Wang; Jun Jin (Food Bioscience, 2024)

Experimental investigation and modelling of the mechanical behaviors of fine/coarse soil mixture - Yu Su; Yu-Jun Cui; Jean-Claude Dupla; Jean Canou (Transportation Geotechnics, 2024)

Evaluation of potential evapotranspiration models over fluxdata network cropland sites - Ziling He; Shouzheng Jiang; Yu Feng; Lu Zhao; Jun Li; Yuting Zhang; Ningbo Cui (Journal of Hydrology, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Effects of Salinity and Alkalinity on the Volumetric Deformation of the Opalinus Clay from the Lower Sandy Facies (LSF) of Mont Terri Site - Yara Barakat; Nadia Mokni; Yu-Jun Cui; Frédéric Bernier (Rock Mechanics and Rock Engineering, 2024)

Mechanical properties of teguline clay pellet mixtures during continuous oedometric compression - Peng-Ju Qin; Marsheal Fisonga; Yong-Feng Deng; Yu-Jun Cui; Wei-Min Ye (Applied Clay Science, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Alkali-modified biomass ash enhances the adsorption capacities of Cu2+, Cd2+, and Pb2+ and their immobilization in soil - Hongbiao Cui; Wenli Yu; Shuai Li; Shiwen Zhang; Shaojun Hu; Jun Zhou (Journal of Environmental Chemical Engineering, 2024)

Exosomes from Hypoxia-treated Mesenchymal Stem Cells: Promoting Neuroprotection in Ischemic Stroke Through miR-214-3p/PTEN Mechanism - Qian Wu; Jia-Huan Wu; Zhi-Yuan Ye; Wen She; Wen-Jie Peng; Hui-Xin Zhang; Cui Qi; Tian Tian; Xiao-Yu Hou; Jun Gao (Molecular Neurobiology, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Global associations between long-term exposure to PM2.5 constituents and health: A systematic review and meta-analysis of cohort studies - Sujuan Chen; Di Liu; Lin Huang; Cui Guo; Xiaoke Gao; Zhiwei Xu; Zhou Yang; Yu Chen; Mengmeng Li; Jun Yang (Journal of Hazardous Materials, 2024)

Missing microbes in infants and children in the COVID-19 pandemic: a study of 1,126 participants in Beijing, China - Jiejing Wang; Yuejuan Li; Yu Mu; Kefei Huang; Danyi Li; Canhui Lan; Yutao Cui; Jun Wang (Science China Life Sciences, 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Amphidiploid production of a distant hybrid Populus simonii × P. euphratica cv. ‘Xiaohuyang-1’ and resulting in phenotypic variation - Ying Zhang; Zi-Yu Wang; Xiao-Tong Cui; Xiao-Xiao Zhang; Jin-Wang Zhang; Long Tie; Jun Wang (New Forests, 2024)

Large greenhouse gases emissions from lakes in Inner Mongolia, China - Heyang Sun; Ruihong Yu; Xinyu Liu; Zhuangzhuang Zhang; Xiaohui Ren; Xiangwei Li; Zhen Qi; Jun Wang; Zhiwei Guo; Penghang Zhu; Xixi Lu; Baoshan Cui (Journal of Hydrology, 2024)

Volume change characteristic of compacted bentonite during hydration upon high suction change: Experimental study and constitutive simulation - Yang Wang; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2024)

Ozone-delivering nanocomposite hydrogel for acute Staphylococcus aureus osteomyelitis treatment via neutrophil regulation - Hangtian Wu; Yihuang Lin; Yanpeng Lin; Mingye Deng; Jiahui Hou; Dahai Liu; Zhuang Cui; Daogang Guan; Jun Wang; Bin Yu (Chemical Engineering Journal, 2024)

Spatial and diel variations of bacterioplankton and pico-nanoeukaryote communities and potential biotic interactions during macroalgal blooms - Cui He; Guihao Li; Songbao Zou; Pengfei Zheng; Qinqin Song; Guanzhe Li; Qin Yu; Yunjun Yu; Qianqian Zhang; Xiaoli Zhang; Zhuo Shen; Jun Gong (Marine Pollution Bulletin, 2024)

T-2 toxin-induced damage to articular cartilage in rats coincided with impaired autophagy linked to the HIF-1α/AMPK signaling axis - Fang Qi; Si-Lu Cui; Bing Zhang; Hao-Nan Li; Jun Yu (Toxicon, 2024)

Immobilisation remediation of arsenic-contaminated soils with promising CaAl-layered double hydroxide and bioavailability, bioaccessibility, and speciation-based health risk assessment - Xiao-Chen Chen; Zhen-Jia Huang; Ao Wang; Jian-Ying Yu; Jian-Yu Zhang; Zi-Jun Xiao; Xiao-Yu Cui; Xian-Hua Liu; Nai-Yi Yin; Yan-Shan Cui (Journal of Hazardous Materials, 2024)

Influences of coexisting aged polystyrene microplastics on the ecological and health risks of cadmium in soils: A leachability and oral bioaccessibility based study - Xiao-Chen Chen; Ao Wang; Jun-Jie Wang; Zeng-Di Zhang; Jian-Ying Yu; Ying-Jie Yan; Jian-Yu Zhang; Jia Niu; Xiao-Yu Cui; Xian-Hua Liu (Journal of Hazardous Materials, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Author Correction: Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

A dual-mode portable platform with spatiotemporal temperature–pressure signal readouts for ultrasensitive quantitative determination of cancer cells - Min Tian; Jun Wang; Wang Xiang; Zhi Zheng; Zhonghui Luo; Shihan Jing; Yuxi Zheng; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2024)

Investigating the fatigue performance of conventional reinforced concrete CRTS III ballastless track structures using a fatigue damage constitutive model - Li Song; Jiarui Shi; Jun Wu; Chenxing Cui; Ran Liu; Zhiwu Yu (Engineering Structures, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

A novel tool for tracing water sources of streamflow in a mixed land-use catchment - Zhi-Xiang Sun; Jun-Fang Cui; Jian-Hua Cheng; Xiang-Yu Tang (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Spectroscopic analysis on effluent organic matter (EfOM) evolution in different UV-based advanced oxidation processes - Donghai Yuan; Ruiying Wu; Dayang Yu; Meng Liu; Hantong Qie; Siyu Xiong; Meng Ren; Jun Cui (Journal of Cleaner Production, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Uncovering the origin of surface-redox pseudocapacitance of molybdenum phosphides enables high-performance flexible sodium-ion capacitors - Yalong Jiang; Runya Han; Jun Dong; Ruohan Yu; Shuangshuang Tan; Fangyu Xiong; Qiulong Wei; Junjun Wang; Lianmeng Cui; Haiyang Tian; Yingkui Yang; Qinyou An (Chemical Engineering Journal, 2023)

Buckling Failure Mechanism of a Rock Plate Under Multi-directional Constraints - Yang-Yang Cui; Yang-Yi Zhou; Xiao-Jun Yu; Fei-Yan Wang (Rock Mechanics and Rock Engineering, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

A negative feedback bionic hydrogel reverses damaged cartilage microenvironment and induces targeted BMSCs differentiation for cartilage regeneration - Zhi Zheng; Jian Sun; Jun Wang; Suisui He; Yun Huang; Xu Yang; Yuqi Zhao; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

A smartphone-integrated portable platform based on polychromatic ratiometric fluorescent paper sensors for visual quantitative determination of norfloxacin - Jiaheng Zhang; Jun Wang; Feijun Ouyang; Zhi Zheng; Xiaowan Huang; Haitao Zhang; Dongxiu He; Suisui He; Hua Wei; Cui-Yun Yu (Analytica Chimica Acta, 2023)

Effects of magnetic field direction on O + vertical transport in the Martian ionosphere - Shi-bang Li; Hao-yu Lu; Jin-bin Cao; Jun Cui; Yun Li; Guo-kan Li; Ni-han Chen; Jian-xuan Wang (Advances in Space Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A model for describing advective and diffusive gas transport through initially saturated bentonite with consideration of temperature - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2023)

Microstructural investigation into the damage behaviour of MX80 bentonite pellet under wetting/drying path using Mercury Intrusion Porosimetry (MIP) and Micro-Computed Tomography (μCT) - Jin-Wen Yang; Yu-Jun Cui; Nadia Mokni; Emmanuel Ormea (Engineering Geology, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Modelling the permanent strain of fine/coarse soil mixture with consideration of the effects of coarse grain content and suction by incorporating soil–water retention curve - Yu Su; Yu-Jun Cui; Jean-Claude Dupla; Jean Canou; Shu-Qian Duan (Bulletin of Engineering Geology and the Environment, 2023)

Diversity, community structure, and quantity of eukaryotic phytoplankton revealed using 18S rRNA and plastid 16S rRNA genes and pigment markers: a case study of the Pearl River Estuary - Shumin Xu; Guihao Li; Cui He; Yi Huang; Dan Yu; Huiwen Deng; Zhuyin Tong; Yichong Wang; Christine Dupuy; Bangqin Huang; Zhuo Shen; Jie Xu; et al. (Marine Life Science & Technology, 2023)
Understanding consistencies and discrepancies in characterizing diversity and quantity of phytoplankton is essential for better modeling ecosystem change. In this study, eukaryotic phytoplankton in the Pearl River Estuary, South China Sea were investigated using nuclear 18S rRNA and plastid 16S or 23S rRNA genes and pigment analysis. It was found that 18S abundance poorly explained the variations in total chlorophyll a (Chl- a ). However, the ratios of log-transformed 18S abundance to Chl- a in the major phytoplankton groups were generally environment dependent, suggesting that the ratio has potential as an indicator of the physiological state of phytoplankton. The richness of 18S-based operational taxonomic units was positively correlated with the richness of 16S-based amplicon sequence variants of the whole phytoplankton community, but insignificant or weak for individual phytoplankton groups. Overall, the 18S based, rather than the 16S based, community structure had a greater similarity to pigment-based estimations. Relative to the pigment data, the proportion of haptophytes in the 18S dataset, and diatoms and cryptophytes in the 16S dataset, were underestimated. This study highlights that 18S metabarcoding tends to reflect biomass-based community organization of eukaryotic phytoplankton. Because there were lower copy numbers of plastid 16S than 18S per genome, metabarcoding of 16S probably approximates cell abundance-based community organization. Changes in biomass organization of the pigment-based community were sensitive to environmental changes. Taken together, multiple methodologies are recommended to be applied to more accurately profile the diversity and community composition of phytoplankton in natural ecosystems.

Association of maternal pre-pregnancy dietary intake with adverse maternal and neonatal outcomes: A systematic review and meta-analysis of prospective studies - Yunfeng Cui; Minqi Liao; Aihua Xu; Gengdong Chen; Jun Liu; Xiaoxuan Yu; Shuna Li; Xingyao Ke; Sixian Tan; Zeyan Luo; Qian Wang; Yanhua Liu; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Release characteristics and toxicity assessment of micro/nanoplastics from food-grade nonwoven bags - Jia Li; Qian Wang; Min Cui; Songguo Yu; Xuehai Chen; Jun Wang (Science of The Total Environment, 2023)

GR1 and NTRA involved in pollen tube growth in the stigma of Arabidopsis - Ming Jun Zhang; Jing Jing Cui; Zi Ming Wang; Yu Xiu Dong; Xin-Qi Gao (Planta, 2023)

Uncertainty quantification of CO2 emissions from China's civil aviation industry to 2050 - Lishan Yang; Yu-Jie Hu; Honglei Wang; Chengjiang Li; Bao-Jun Tang; Binli Wang; Hefu Cui (Journal of Environmental Management, 2023)

On the hydro-mechanical behaviour of unsaturated damaged Callovo-Oxfordian claystone - Hao Wang; Yu-Jun Cui; Minh Ngoc Vu; Feng Zhang; Jean Talandier (Engineering Geology, 2023)

Changes in molybdenum bioaccessibility in four spiked soils with respect to soil pH and organic matter - Yangxiaoxiao Shi; Yunjiang Yu; Mingdeng Xiang; Peixin Cui; Jiaqi Cui; Feng Zhang; Jun Jiang; Renkou Xu (Journal of Environmental Management, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Regulating the in situ generation of active chlorine species in a photoelectrochemical system for the efficient simultaneous removal of ammonia nitrogen and refractory pharmaceuticals - Yu Zhang; Jun Cui; Yuansheng Pei (Chemical Engineering Journal, 2023)

A uw-Cellular Network: Design, Implementation and Experiments - Jifeng Zhu; Xiaohe Pan; Zheng Peng; Mengzhuo Liu; Jingqian Guo; Tong Zhang; Yu Gou; Jun-Hong Cui (Journal of Marine Science and Engineering, 2023)
The most significant increase of current task is in the desire for operational flexibility and agility in large-scale underwater network application scenarios in recent years. In order to address the challenging problems in Underwater Wireless Sensor Networks (UWSNs), we propose a large-scale UWSN based on the cellular network architecture called Underwater Cellular (uw-Cellular) network. It is designed especially for application scenarios where a large number of both fixed and mobile network nodes exist in a wide area to monitor the underwater environment. We also design protocols in each network layer in order to ensure reasonable channel sharing, data forwarding path selection and data reliability. The purpose of the simulation study we implement is to evaluate the performance of the CLA routing strategy compared to the VBF and the MFLOOD protocols in the uw-Cellular network. We also deploy a twenty-node uw-Cellular network in the real-world environment as the field case study. The experimental results showed that the Data Rate between any nodes could reach above 500 bps, and the network Average Throughput was no less than 550 bps under various load situations.

In utero exposure to perfluoroalkyl substances and early childhood BMI trajectories: A mediation analysis with neonatal metabolic profiles - Xiaojing Zeng; Ting Chen; Yidan Cui; Jian Zhao; Qian Chen; Zhangsheng Yu; Yongjun Zhang; Lianshu Han; Yan Chen; Jun Zhang (Science of The Total Environment, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

“Two-in-one” dual-function luminescent MOF hydrogel for onsite ultra-sensitive detection and efficient enrichment of radioactive uranium in water - An-Qi Cui; Xiao-Yi Wu; Jun-Bin Ye; Gang Song; Di-Yun Chen; Jie Xu; Yu Liu; Jia-Ping Lai; Hui Sun (Journal of Hazardous Materials, 2023)

Experimental investigation and modeling of the mechanical behaviour of Yanji swelling mudstone subjected to wetting-drying-freezing-thawing cycles - Zhixiong Zeng; Ling-Wei Kong; Yu-Jun Cui (Transportation Geotechnics, 2023)

Screening and characterization of a novel antifreeze peptide from silver carp muscle hydrolysate - Meili Cui; Jialei Li; Jun Li; Faxiang Wang; Xianghong Li; Jian Yu; Yiqun Huang; Yongle Liu (Food Chemistry, 2023)

Distribution, source identification and ecological effects of aerosol dissolved nutrients in the Bohai Bay - Xudong Cui; Liying Peng; Yu Guo; Guicheng Zhang; Haijiao Liu; Yujian Wen; Guodong Zhang; Jun Sun (Environmental Pollution, 2023)

Application of logistic regression model for hazard assessment of landslides caused by the 2012 Yiliang Ms 5.7 earthquake in Yunnan Province, China - Jia-le Jin; Yu-long Cui; Chong Xu; Jun Zheng; Hai-bo Miao (Journal of Mountain Science, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Within-day variability, predictors, and risk assessments of exposure to parabens among Chinese adult men - Yu Miao; Pan-Pan Chen; Min Zhang; Fei-Peng Cui; Chong Liu; Yan-Ling Deng; Jia-Yue Zeng; Wen-Jun Yin; Qiang Zeng (Environmental Research, 2023)

Effect of biochar incorporation on phosphorus supplementation and availability in soil: a review - Yangxiaoxiao Shi; Yuanchun Yu; E Chang; Ruhai Wang; Zhineng Hong; Jiaqi Cui; Feng Zhang; Jun Jiang; Renkou Xu (Journal of Soils and Sediments, 2023)

Study of the effect of seismic performance measures on a metro station structure in liquefiable soil - Yiliang Yu; Xiaohua Bao; Xiangsheng Chen; Jun Shen; Shanyong Wang; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Modified biochar/humic substance/fertiliser compound soil conditioner for highly efficient improvement of soil fertility and heavy metals remediation in acidic soils - Meng Liu; Xiao Tan; Mingxia Zheng; Dayang Yu; Aijun Lin; Jiaoxian Liu; Chunyan Wang; Zhiyun Gao; Jun Cui (Journal of Environmental Management, 2023)

Decreased in vitro bioaccessibility of Cd and Pb in an acidic Ultisol through incorporation of crop straw-derived biochar - Jiaqi Cui; Yunjiang Yu; Mingdeng Xiang; Yangxiaoxiao Shi; Feng Zhang; Di Fang; Jun Jiang; Renkou Xu (Environmental Pollution, 2023)

Amygdalin alleviated TGF-β-induced epithelial-mesenchymal transition in bronchial epithelial cells - An-nan Zhang; Nan Li; Zhuo-chang Chen; Ya-li Guo; Cui-jie Tian; Dong-jun Cheng; Xue-yi Tang; Xiao-yu Zhang (Chemico-Biological Interactions, 2023)

Characterization of carbonaceous matter emitted from residential coal and biomass combustion by experimental simulation - Min Cui; Yuanyuan Xu; Binbin Yu; Caiqing Yan; Jun Li; Mei Zheng; Yingjun Chen (Atmospheric Environment, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

CACNA1C-AS2 inhibits cell proliferation and suppresses cell migration and invasion via targeting FBXO45 and PI3K/AKT/mTOR pathways in glioma - Tong Cao; Yue Cui; Yingying Wang; Linhui Wu; Ke Yu; Kai Chen; Jun Xia; Yuyun Li; Zhiwei Peter Wang; Jia Ma (Apoptosis, 2022)

Developing a Method for Preparing Callovo-Oxfordian Claystone Samples at a Desired Damage Level in Triaxial Cell - Hao Wang; Yu-Jun Cui; Minh-Ngoc Vu; Jean Talandier; Nathalie Conil (Rock Mechanics and Rock Engineering, 2022)

Effect of organic matter content on Atterberg limits and undrained shear strength of river sediment - Gang Wang; Xia Bian; Ye-Jiao Wang; Yu-Jun Cui; Ling-Ling Zeng (Marine Georesources & Geotechnology, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Coupled effects of saline solution and vertical stress on swelling deformation of compacted GMZ bentonite/sand mixtures - Yong-Gui Chen; Yu-Hao Hu; Kan Pan; Wei-Min Ye; Yu-Jun Cui (Bulletin of Engineering Geology and the Environment, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Landslides triggered by the 1970 Ms 7.7 Tonghai earthquake in Yunnan, China: an inventory, distribution characteristics, and tectonic significance - Yu-long Cui; Jun-hong Hu; Chong Xu; Hai-bo Miao; Jun Zheng (Journal of Mountain Science, 2022)

Desferrioxamine Ameliorates Lipopolysaccharide-Induced Lipocalin-2 Upregulation via Autophagy Activation in Primary Astrocytes - Juntao Cui; Yu Yuan; Jun Wang; Ning Song; Junxia Xie (Molecular Neurobiology, 2022)

A procedure for interaction between rock mass and liner for deep circular tunnel based on new solution of longitudinal displacement profile - Qiang Shen; Jun-Jie Zheng; Lan Cui; Yu Pan; Bo Cui (European Journal of Environmental and Civil Engineering, 2022)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

In Vivo Intravascular Pacing Using a Wireless Microscale Stimulator - Parinaz Abiri; Sandra Duarte-Vogel; Tzu-Chieh Chou; Arash Abiri; Varun Gudapati; Alireza Yousefi; Mehrdad Roustaei; Chih-Chiang Chang; Qingyu Cui; Jeffrey J. Hsu; Malcolm Bersohn; Dejan Markovic; et al. (Annals of Biomedical Engineering, 2021)

Activity of eugenol derivatives against Fusarium graminearum Q1 strain and screening of isoeugenol mixtures - Wen Cui; Kai-Yue Du; Yu-Xuan Ling; Cong-Jun Yang (Journal of Plant Pathology, 2021)

A catastrophic natural disaster chain of typhoon-rainstorm-landslide-barrier lake-flooding in Zhejiang Province, China - Yu-long Cui; Jun-hong Hu; Chong Xu; Jun Zheng; Jiang-bo Wei (Journal of Mountain Science, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Expression characteristics of immune factors in secondary lymphoid organs of newborn, juvenile and adult yaks (Bos grunniens) - Yufeng Huang; Yan Cui; Sijiu Yu; Penggang Liu; Jun Liu; Jun-Feng He; Juan Sun (Cell and Tissue Research, 2020)

The sorption performance of corroded Gaomiaozi bentonite by evolved cement water at different temperatures: the case of europium removal - Zhao Sun; Yong-gui Chen; Yinghui Shang; Yu-jun Cui; Wei-min Ye; Dong-bei Wu (Environmental Science and Pollution Research, 2020)

Regional differential decomposition and convergence of rural green development efficiency: evidence from China - Cui Yu; Liu Wenxin; Sufyan Ullah Khan; Cai Yu; Zhu Jun; Deng Yue; Minjuan Zhao (Environmental Science and Pollution Research, 2020)

Influence of Soil Properties and Aging on Antimony Toxicity for Barley Root Elongation - Peng Zhang; Tong-Liang Wu; Syed Tahir Ata-Ul-Karim; Yuan-Ying Ge; Xu Cui; Dong-Mei Zhou; Yu-Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

Assessment of Swelling Pressure Determination Methods with Intact Callovo-Oxfordian Claystone - Feng Zhang; Yu-Jun Cui; Nathalie Conil; Jean Talandier (Rock Mechanics and Rock Engineering, 2020)

Rapid detection of Anguina agrostis by loop-mediated isothermal amplification - Lu-zhen Yu; Shao-yi Song; Cui Yu; Bin-bin Jiao; Yi-min Tian; You-jun Li (European Journal of Plant Pathology, 2020)

Chemical content and source apportionment of 36 heavy metal analysis and health risk assessment in aerosol of Beijing - Limeng Cui; Zhuona Wu; Peng Han; Yasuyuki Taira; Huan Wang; Qinghua Meng; Zechen Feng; Shuguang Zhai; Jun Yu; Weijie Zhu; Yuxia Kong; Hongfang Wang; et al. (Environmental Science and Pollution Research, 2020)

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Benthic foraminiferal fauna and sediment provenance of Eocene syn-rift sequences in Taiwan: implication for onset of Asian epi-continental marginal seas off China coast - Chi-Yue Huang; Lei Shao; Ming-Huei Wang; Wei-Guang Xue; Pei-Jun Qiao; Yu-Chi Cui; Yuan-Li Hou (Marine Geophysical Research, 2019)

Protective effect of dihydromyricetin on hyperthermia-induced apoptosis in human myelomonocytic lymphoma cells - Qian-Wen Feng; Zheng-Guo Cui; Yu-Jie Jin; Lu Sun; Meng-Ling Li; Shahbaz Ahmad Zakki; De-Jun Zhou; Hidekuni Inadera (Apoptosis, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Correction to: Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2019)

Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2018)

Compression reference of soil structure evaluation with reconstituted clays at different initial water contents - Ling-Ling Zeng; Zhen-Shun Hong; Yu-Jun Cui; Martin D. Liu (Marine Georesources & Geotechnology, 2018)

Ascidiaceibacter salegens gen. nov., sp. nov., isolated from an ascidian - Lei Chen; Shi-Cheng Wang; Cui-Hong Ma; Dong-Xu Zheng; Zong-Jun Du; Guang-Yu Wang (Antonie van Leeuwenhoek, 2018)

Experimental infection of Marmota monax with a novel hepatitis A virus - Jie-mei Yu; Li-li Li; Guang-cheng Xie; Cui-yuan Zhang; Yuan-yun Ao; Zhao-jun Duan (Archives of Virology, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

A loop mediated isothermal amplification (LAMP) assay for rapid and reliable detection of Anguina wevelli, a grass parasitic nematode - Lu-zhen Yu; Shao-yi Song; Cui Yu; Long-jun Qi; Zi-xiang Yu; Bin-bin Jiao; Juan Yang (European Journal of Plant Pathology, 2018)

Centrifuge model test of an irrigation-induced loess landslide in the Heifangtai loess platform, Northwest China - Sheng-hua Cui; Xiang-jun Pei; Hao-yu Wu; Run-qiu Huang (Journal of Mountain Science, 2018)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

Erratum to: Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Characteristics and triggering mechanism of Xinmo landslide on 24 June 2017 in Sichuan, China - Li-jun Su; Kai-heng Hu; Wei-feng Zhang; Jiao Wang; Yu Lei; Chong-lei Zhang; Peng Cui; Alessandro Pasuto; Quan-hong Zheng (Journal of Mountain Science, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Comparative Studies on the Toxicokinetics of Benzo[a]pyrene in Pinctada martensii and Perna viridis - Haihua Wang; Lili Cui; Huamin Cheng; Yu Zhang; Xiaoping Diao; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Adsorption of Dioxin by Bag Filter + Powdered Activated Carbon - Yu-Yong Cui; Guo-Hua Yang; Gui-Hui Xiao; Jiang-Hua Zhou; Guo-Zhu Ding; Xue-Jun Pan (Water, Air, & Soil Pollution, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

iTRAQ-Based Comparative Proteomics Analysis of the Fruiting Dikaryon and the Non-fruiting Monokaryon of Flammulina velutipes - Jing-Yu Liu; Ming-chang Chang; Jun-long Meng; Cui-ping Feng; Yong-nan Liu (Current Microbiology, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Association of interleukin-1 family cytokines single nucleotide polymorphisms with susceptibility to systemic sclerosis: an independent case–control study and a meta-analysis - Xiao-Lei Huang; Guo-Cui Wu; Yu-Jie Wang; Xiao-Ke Yang; Guo-Jun Yang; Jin-Hui Tao; Yu Duan; Jun-Wei Yan; Xiang-Pei Li; Dong-Qing Ye; Jing Wang (Immunologic Research, 2016)

Therapeutical Strategies for Spinal Cord Injury and a Promising Autologous Astrocyte-Based Therapy Using Efficient Reprogramming Techniques - Hao Yang; Cui-cui Liu; Chun-Yu Wang; Qian Zhang; Jiang An; Lingling Zhang; Ding-Jun Hao (Molecular Neurobiology, 2016)

Microbial metabolism induced chain shortening of polyacrylamide with assistance of bioelectricity generation - Min Sun; Zhong-Hua Tong; Yu-Zhi Cui; Jun Wang (Environmental Science and Pollution Research, 2016)

Alleviating effects of exogenous NO on tomato seedlings under combined Cu and Cd stress - Yi-jun Wang; Yu-Xiu Dong; Juan Wang; Xiu-min Cui (Environmental Science and Pollution Research, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Discontinuous slope failures and pore-water pressure variation - Xiao-jun Guo; Yong Li; Peng Cui; Wan-yu Zhao; Xing-yuan Jiang; Yan Yan (Journal of Mountain Science, 2016)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Acetylation of lysine 9 on histone H3 is associated with increased pro-inflammatory cytokine release in a cigarette smoke-induced rat model through HDAC1 depression - Xi Chen; Xiao-jun Guan; Xiao-hua Peng; Zhi-lei Cui; Chun-yu Luan; Xue-jun Guo (Inflammation Research, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

Expression Analysis and Binding Assays in the Chemosensory Protein Gene Family Indicate Multiple Roles in Helicoverpa armigera - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Jing Zhu; Jin-Jie Cui; Shuang-Lin Dong (Journal of Chemical Ecology, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Ameliorating Effects of Combined Curcumin and Desferrioxamine on 6-OHDA-Induced Rat Mode of Parkinson’s Disease - Hua Lv; Jun Liu; Li Wang; Hong Zhang; Shuqi Yu; Zhiwei Li; Feng Jiang; Yu Niu; Jie Yuan; Xiaoli Cui; Wenxiu Wang (Cell Biochemistry and Biophysics, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Activated macrophage-like synoviocytes are resistant to endoplasmic reticulum stress-induced apoptosis in antigen-induced arthritis - Li-Jie Feng; Tong-Cui Jiang; Cheng-Yue Zhou; Chang-Liang Yu; Yu-Jun Shen; Jun Li; Yu-Xian Shen (Inflammation Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

The discovery of archaea origin phosphomannomutase in algae based on the algal transcriptome - Yanjing Feng; Shan Chi; Cui Liu; Shengping Chen; Jun Yu; Xumin Wang; Tao Liu (Acta Oceanologica Sinica, 2014)

Endogenous viral elements in algal genomes - Liang Wang; Shuangxiu Wu; Tao Liu; Jing Sun; Shan Chi; Cui Liu; Xingang Li; Jinlong Yin; Xumin Wang; Jun Yu (Acta Oceanologica Sinica, 2014)

Tryptophan synthase of Phaeophyceae originated from the secondary host nucleus - Yalan Zhang; Shan Chi; Shuangxiu Wu; Cui Liu; Jun Yu; Xumin Wang; Shengping Chen; Tao Liu (Acta Oceanologica Sinica, 2014)

Comparative analysis of four essential Gracilariaceae species in China based on whole transcriptomic sequencing - Jiayue Xu; Jing Sun; Jinlong Yin; Liang Wang; Xumin Wang; Tao Liu; Shan Chi; Cui Liu; Lufeng Ren; Shuangxiu Wu; Jun Yu (Acta Oceanologica Sinica, 2014)

De novo sequencing and comparative analysis of three red algal species of Family Solieriaceae to discover putative genes associated with carrageenan biosysthesis - Lipu Song; Shuangxiu Wu; Jing Sun; Liang Wang; Tao Liu; Shan Chi; Cui Liu; Xingang Li; Jinlong Yin; Xumin Wang; Jun Yu (Acta Oceanologica Sinica, 2014)

Comparative analysis on transcriptome sequencings of six Sargassum species in China - Guoliang Wang; Jing Sun; Guiming Liu; Liang Wang; Jun Yu; Tao Liu; Shan Chi; Cui Liu; Haiyan Guo; Xumin Wang; Shuangxiu Wu (Acta Oceanologica Sinica, 2014)

Analysis of Saccharina japonica transcriptome using the high-throughput DNA sequencing technique and its vanadium-dependent haloperoxidase gene - Xiayuan Liang; Xumin Wang; Shan Chi; Shuangxiu Wu; Jing Sun; Cui Liu; Shengping Chen; Jun Yu; Tao Liu (Acta Oceanologica Sinica, 2014)

Transcriptome characterization of Ishige okamurae (Phaeophyceae) shows strong environmental acclimation - Jieqiong Qu; Xumin Wang; Shan Chi; Shuangxiu Wu; Jing Sun; Cui Liu; Shengping Chen; Jun Yu; Tao Liu (Acta Oceanologica Sinica, 2014)

Transcriptome-wide evolutionary analysis on essential brown algae (Phaeophyceae) in China - Jing Sun; Liang Wang; Shuangxiu Wu; Xumin Wang; Jingfa Xiao; Shan Chi; Cui Liu; Lufeng Ren; Yuhui Zhao; Tao Liu; Jun Yu (Acta Oceanologica Sinica, 2014)

Transcriptome sequencing of essential marine brown and red algal species in China and its significance in algal biology and phylogeny - Shuangxiu Wu; Jing Sun; Shan Chi; Liang Wang; Xumin Wang; Cui Liu; Xingang Li; Jinlong Yin; Tao Liu; Jun Yu (Acta Oceanologica Sinica, 2014)

Using a mesoscale ensemble to predict forecast error and perform targeted observation - Jun Du; Rucong Yu; Chunguang Cui; Jun Li (Acta Oceanologica Sinica, 2014)

An experimental study on the shear strength behaviour of an interlayered shear weakness zone - Ding-Ping Xu; Xia-Ting Feng; Yu-Jun Cui (Bulletin of Engineering Geology and the Environment, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

New precursor of tetraterpenoids from the soft coral Sarcophyton glaucum - Cui-Xian Zhang; Xi-Xin He; Jun Zhang; Qiong Guo; Ling-Fang Lei; Jing-Yu Su; Long-Mei Zeng (Natural Product Research, 2013)

Sorption isotherms and kinetics of Sb(V) on several Chinese soils with different physicochemical properties - Jian-Xin Fan; Yu-Jun Wang; Xiao-Dan Cui; Dong-Mei Zhou (Journal of Soils and Sediments, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Beta2-Adrenergic Receptor and Astrocyte Glucose Metabolism - Jun-hong Dong; Xin Chen; Min Cui; Xiao Yu; Qi Pang; Jin-peng Sun (Journal of Molecular Neuroscience, 2012)

Identification and Binding Characterization of Three Odorant Binding Proteins and One Chemosensory Protein from Apolygus lucorum (Meyer-Dur) - Jin-Feng Hua; Shuai Zhang; Jin-Jie Cui; Dao-Jie Wang; Chun-Yi Wang; Jun-Yu Luo; Li-Min Lv (Journal of Chemical Ecology, 2012)

Remediation of saturated Shanghai sandy silt contaminated with p-xylene using air sparging - Yong-Gui Chen; Wei-Min Ye; Zi-Jun Xie; Bao Chen; Yu-Jun Cui (Natural Hazards, 2012)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)

Effects of SKF-96365, a TRPC inhibitor, on melittin-induced inward current and intracellular Ca2+ rise in primary sensory cells - Jing Ding; Yong Xiao; Dan Lu; Yi-Ru Du; Xiu-Yu Cui; Jun Chen (Neuroscience Bulletin, 2011)

Interactive effect of fluoride burden with calcitonin receptor gene polymorphisms on the risk of F bone injury - Jun Tu; Kejian Liu; Yu’e Song; Yuzeng Zhang; Caiyan Cui; Cuirong Lu (International Archives of Occupational and Environmental Health, 2011)

Analysis and characterization of the complete genome of a member of a new species of kobuvirus associated with swine - Jie-mei Yu; Zi-qian Xu; Bo-wen Li; Qing Zhang; Shu-xian Cui; Miao Jin; Zhao-jun Duan (Archives of Virology, 2011)

Binding Characterization of Recombinant Odorant-binding Proteins from the Parasitic Wasp, Microplitis mediator (Hymenoptera: Braconidae) - Shuai Zhang; Li-Zhen Chen; Shao-Hua Gu; Jin-Jie Cui; Xi-Wu Gao; Yong-Jun Zhang; Yu-Yuan Guo (Journal of Chemical Ecology, 2011)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)

Virgibacillus zhanjiangensis sp. nov., a marine bacterium isolated from sea water - Qing-Zhong Peng; Jun Chen; Yu-Qin Zhang; Qi-Hui Chen; De-Jiao Peng; Xiao-Long Cui; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Halobacillus hunanensis sp. nov., a moderately halophilic bacterium isolated from a subterranean brine - Qing-Zhong Peng; Qing-Jing Peng; Yu-Qin Zhang; Zhu-Xiang Liu; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Vapour Equilibrium and Osmotic Technique for Suction Control - James A. Blatz; Yu-Jun Cui; Luciano Oldecop (Geotechnical and Geological Engineering, 2008)

Water Balance and Evapotranspiration Monitoring in Geotechnical and Geoenvironmental Engineering - Yu-Jun Cui; Jorge G. Zornberg (Geotechnical and Geological Engineering, 2008)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)